Calculus 1.Final Exam.Solutions.Practice 1
Calculus 1.Final Exam.Solutions.Practice 1
Calculus 1.Final Exam.Solutions.Practice 1
1. (5 pts) A B C D E
2. (5 pts) A B C D E
3. (5 pts) A B C D E
4. (5 pts) A B C D E
5. (5 pts) A B C D E
6. (5 pts) A B C D E
7. (5 pts) A B C D E
8. (5 pts) A B C D E
1
9. (15 pts) cm/s
108π
2 48
12. (15 pts) y=− x+
11 11
9
Calculus 1 Final Exam Solutions
f (x) = 14 − 2x
1 1
f′(x) = (14 − 2x)− 2 ⋅ −2
2
1
f′(x) = −
14 − 2x
x 2 + 7x + 10
f (x) = 2
x − 3x − 10
(x + 2)(x + 5)
f (x) =
(x + 2)(x − 5)
x+5
f (x) =
x−5
10
3. B. Break down the limit
lim x 2 + 1 = 17
x→4
• x approaches 4
lim g(x)
x→4
lim 2x + 3
x→4
2(4) + 3
11
Find f (11).
f (11) = 2(11)3
11
f (11) = 2(1,331)
f (11) = 2,662
1
= e kt
2
1
ln = ln e kt
2
1
ln = kt
2
1
ln 2
k=
t
ln 1 − ln 2
k=
t
0 − ln 2
k=
t
ln 2
k=−
t
12
Because k is a constant, we can absorb the negative sign into it.
ln 2
k=
t
Substitute t = 68.9.
ln 2
k=
68.9
k ≈ 0.0101
f (x)
lim
x→−1 4g(x)
f (x)
lim
x→−1 4g(x)
x 2 + 4x + 3
lim
x→−1 4(2x − 1)
Now we’ll substitute the value we’re approaching into the function.
(−1)2 + 4(−1) + 3
4(2(−1) − 1)
1−4+3
4(−2 − 1)
13
0
−12
0 = − 0.8x + 500
0.8x = 500
x = 625
T(t) = 6e −t
T(t) = 6e −1
T(t) ≈ 6(0.37)
14
T(t) ≈ 2.2 ≈ 2∘ C
4 3
V= πr
3
dV 4 dr
(1) = π(3r 2)
dt 3 dt
dV 2 dr
= 4πr
dt dt
dr
3 = 4π(9)2
dt
dr
3 = 324π
dt
dr 3
=
dt 324π
dr 1
=
dt 108π
15
10. Both the interest rate and time have units in years, so we have
matching units, which means we can plug directly into the
exponential growth formula to find the number of years we’ve held
the investment.
A(t) = A0e rt
4.2867 = e 0.048t
ln 4.2867 = 0.048t
ln 4.2867
t=
0.048
t ≈ 30.3
11. Take the derivative of the position function to get the velocity
function.
s(t) = − 8t 2 + 4t − 7
s′(t) = − 16t + 4
v(t) = − 16t + 4
16
Substitute t = 2 to find instantaneous velocity at that time.
v(2) = − 16(2) + 4
v(3) = − 28
12x 3 + 72x 2 − 4x 3
f′(x) =
(x + 6)2
8x 3 + 72x 2
f′(x) =
(x + 6)2
8(2)3 + 72(2)2
f′(2) =
(2 + 6)2
8(8) + 72(4)
f′(2) =
82
64 + 288
f′(2) =
64
17
11
f′(2) =
2
This is the slope of the tangent line at (2,4). Since m = 11/2, we’ll take
the negative reciprocal to find n, the slope of the normal line.
2
n=−
11
We’ll plug n = − 2/11 and the point (2,4) into the point-slope formula
for the equation of the line. Once we simplify, we’ll have the
equation of the normal line to the function at (2,4).
y − y1 = n(x − x1)
2
y−4=− (x − 2)
11
2 4
y−4=− x+
11 11
2 4 44
y=− x+ +
11 11 11
2 48
y=− x+
11 11
18
19